PEMBERDAYAAN UMKM DESA KALONGAN MELALUI IMPLEMENTASI SWOT STRATEGY MENUJU UMKM BERKELANJUTAN - Setyahuni, Suhita Whini; Yovita, Lenni; Zakaria, Fakhmi (Jurnal Abdimas Perbanas, 2025)
Kalongan Village MSMEs have great potential to grow into a higher scale. Several obstacles in the production and marketing aspects are still faced by Kalongan Village MSMEs. This community service activity aims to improve the ability of MSME actors in increasing the competitiveness of MSMEs through the SWOT strategy approach. SWOT analysis is useful for supporting the preparation of production and marketing strategies that have an impact on increasing the competitiveness of MSMEs. This activity was attended by 20 MSME partners in Kalongan Village. The method used in this activity is a workshop based on learning by practice. This activity can improve the SWOT analysis skills of MSME actors as evidenced by the increase in pre-test and post-test scores from 65.37 to 87.51. This activity is able to provide an understanding for MSME owners regarding the importance of SWOT strategy and the preparation of SWOT matrix to support the sustainability of MSMEs.